Immunogenicity of trivalent influenza vaccines in patients with chronic kidney disease undergoing hemodialysis: MF59-adjuvanted versus non-adjuvanted vaccines. Issue 11 (1st November 2016) - Noh, Ji Yun; Song, Joon Young; Choi, Won Suk; Lee, Jacob; Seo, Yu Bin; Kwon, Young Joo; Ko, Gang Jee; Cha, Dae Ryong; Kang, Young Sun; Lee, Young-Ki; Cheong, Hee Jin; Kim, Woo Joo
ABSTRACT: Backgrounds : Patients with chronic kidney disease (CKD) are at an increased risk of morbidity and mortality from influenza. However, the immunogenicity of influenza vaccine is known to be attenuated in these patients. In this study, the immunogenicity of MF59-adjuvanted and non-adjuvanted trivalent influenza vaccines was compared in CKD patients undergoing hemodialysis (HD). Methods : During 2013–2014, 179 CKD patients undergoing HD participated in the study. The patients were randomized into either MF59-adjuvanted vaccine group or non-adjuvanted vaccine group and were immunized with the respective vaccine. Sera were collected prior to vaccination and at 1 month (88 patients in MF59-adjuvanted vaccine group and 86 patients in non-adjuvanted vaccine group) and 6 months post vaccination. Levels of hemagglutination inhibition antibodies were measured. Results : The seroconversion rate of all 3 vaccine strains at 1 month post-vaccination was significantly higher in the MF59-adjuvanted group than in the non-adjuvanted group (47.7% vs. 17.4%, A/H1N1; 42.0% vs. 16.3%, A/H3N2; 31.8% vs. 7.0%, B, P < 0.01). One month post-vaccination, the fold increase in geometric mean titer from pre-vaccination for A/H1N1, A/H3N2 and B viruses was significantly greater in the MF59-adjuvanted group than in the non-adjuvanted group. In elderly patients (≥65 years), the seroconversion rate at 1 month post-vaccination against influenza B strain was higher in the MF59-adjuvanted group than in the non-adjuvanted group (33.3% vs. 7.1%, P = 0.03). Conclusion : The MF59-adjuvanted influenza vaccine showed better immunogenicity than the non-adjuvanted influenza vaccine in CKD patients undergoing HD.